Hopf bifurcation and stability crossing curves in a cobweb model with heterogeneous producers and time delays. (November 2015) - Gori, Luca; Guerrini, Luca; Sodini, Mauro
Abstract: We study a continuous time cobweb model with discrete time delays where heterogeneous producers behave as adapters in the market. Specifically, they partially adjust production (which is subject to some gestation lags) towards the profit-maximising quantity under static expectations. The dynamics of the economy is described by a two-dimensional system of delay differential equations. We characterise stability properties of the stationary state of the system and show the emergence of Hopf bifurcations. We also apply some recent mathematical techniques (stability crossing curves) to show how heterogeneous time delays affect the stability of the economy.